Pengelolaan Sampah Rumah Tangga Pemukiman Atas Rawa dengan Metode Eco-enzyme dan Eco-brick pada Kelompok Ibu PKK - Nuning Irnawulan Ishak; Ilhamiyah Ilhamiyah; Satriadi Satriadi; Ermayanti Ishak (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
PKM partners are PKK women's group AthaNia RT.24 in Berangas Timur Village, Alalak District, Barito Kuala Regency, South Kalimantan Province. Waste management is still an environmental problem, one of which is in RT.24. Supported by the condition of partners with minimal knowledge, it adds to the problems related to waste management. The objectives of this community service activity are 1) Increase knowledge about waste management, 2) Assistance with equipment and materials to support the manufacture of waste innovation products 3) Training and assistance in the manufacture of waste innovation products, including eco-enzyme technology for organic waste and ecobricks for plastic waste. . PKM partners are a group of 13 women from PKK AthaNia RT.24 in Berangas Timur Village, Alalak District, Barito Kuala Regency, South Kalimantan Province. The approach method used is lectures, discussions, questions and answers and training in waste management (waste recycling). The evaluation was carried out twice with the results of the 72 pres test increasing to 97.5 at the post test. Partners' knowledge and skills are increasing in waste management, such as making eco-enzymes and ecobricks